Organic Food Demand in Turkey: Segmentation From Necessity to Variety - Göktuna, Bilge Öztürk; HAMZAOĞLU, NAZİFE MERVE (Springer Science and Business Media B.V., 2023)
We aim to reveal organic food consumer profile in terms of sociodemographical characteristics and their preferences including their food consumption choices, knowledge, and information on organic label and environmental awareness and describe the obstacles preventing the growth of organic food sector in Turkey. We conducted a consumer survey in the three largest metropolitan areas in Turkey to describe the characteristics of Turkish organic consumers. The results show that they are mostly more mature, married, having higher income, and do physical activities and they are predominantly concerned about health issues, rather than environment- and food-related preferences, and have limited information on organic. We have produced a graph for Turkish organic food demand using the relative reservation prices that the participants have declared. We can see that this demand is segmented: one part is steeper than the other, and for one segment, organic food is a necessity while for the other it is a variety in the food choice.
Keywords: Organic Food; Demand; Information; Labels; Income Efect; Segmentation